Aplikasi Kamus Bahasa Indonesia - Rejang Menggunakan Metode Sequential Searching Berbasis Android - Agung Kharisma (Jurnal PROCESSOR, 2022)
One of the technologies that is currently developed very rapidly is Smartphones, where Android is a necessity for people. Preserving regional languages is very necessary in the midst of increasingly rapid technological developments. This study helps people who do not understand the Rejang language. The Rejang language dictionary application is designed to be able to perform an electronic search function for the Rejang language dictionary. To support the system development method, the reseacher uses the waterfall method. As well as data collection techniques with research methods by means of observation, interviews and literature study. The implementation of the program used by the computer in this application system uses the Java programming language on Android studio version 1.0 with SQLite Database which provides facilities to simplify the process of system creation and product implementation.